The effect of language on economic behavior : examining the causal link between future tense and time preference in the lab - Chen, Josie I. (2020)
Since Chen (2013), a fast-growing body of literature has documented abundant supporting evidence for the linguistic-savings hypothesis. Despite this influx of research, direct causal evidence is limited. In this study, we take advantage of a unique linguistic feature of the Chinese language: speakers can freely choose whether or not to use the future tense when referring to a future event. This flexibility allows us to unobtrusively manipulate the use of “will” in the description of the rewards in a standard time preference task to cleanly examine its effect on intertemporal decisions. However, our results do not lend further empirical support for the linguistic-savings hypothesis.